THE RELATIONSHIP BETWEEN FAT, FIBER, SODIUM, POTASSIUM, AND CALCIUM INTAKE AND HYPERTENSION AMONG ADOLESCENTS IN PALEMBANG - Shafira, Jihan Natra (International Journal of Public Health Science (IJPHS), 2020)
Hypertension is a condition characterized by a rise in systemic arterial blood pressure above the threshold/normal value. The incidence of hypertension can increase due to various risk factors. High intake of dietary fats and sodium, and low of intake of fibers, potassium and calcium are some risk factors of hypertension. Inadequate intake of nutrients is often ignored by adolescents because of their irregular eating patterns. This study aim was to determine the relationship between fat, fiber, sodium, potassium and calcium intake with hypertension among adolescent. A cross sectional study has been conducted in Palembang from July to December 2019. A total of 475 samples were taken by proportioned stratified random sampling technique who fulfilled the inclusion criteria. Data was taken by measuring blood pressure and using a food recall questionnaire for 3 days, then it was estimated through the nutrisurvey software. The data were analyzed by chi square test. This study showed that the incidence of hypertension among adolescent was 23.4%. There was no significant relationship between fiber intake (p = 1,000, OR = 1,844), sodium intake (p = 0,255, OR = 1,602) potassium intake (p = 1,000, OR = 1,532) and calcium intake (p = 0,316, OR = 3,750) with hypertension. A significant relationship was found between fat intake and hypertension (p = 0,000, OR = 3,425) among adolescents in Palembang.